2009
DOI: 10.1016/j.bbamcr.2008.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Disturbed nuclear orientation and cellular migration in A-type lamin deficient cells

Abstract: The nuclear lamina and the cytoskeleton form an integrated structure that warrants proper mechanical functioning of cells. We have studied the correlation between structural alterations and migrational behaviour in fibroblasts with and without A-type lamins. We show that loss of A-type lamins causes loss of emerin and nesprin-3 from the nuclear envelope, concurring with a disturbance in the connection between the nucleus and the cytoskeleton in A-type lamin-deficient (lmna -/-) cells. In these cells functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
65
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 49 publications
5
65
0
Order By: Relevance
“…S1A). These results indicate that defective nuclear movement in cells expressing lamin A variants that cause muscle disease interferes with cell migration, consistent with earlier studies (18,24).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…S1A). These results indicate that defective nuclear movement in cells expressing lamin A variants that cause muscle disease interferes with cell migration, consistent with earlier studies (18,24).…”
Section: Resultssupporting
confidence: 81%
“…Loss of lamin A results in impaired cell migration (18,24). We tested whether disease-causing lamin A variants affected cell migration by expressing the variants in wound edge cells and stimulating migration with serum.…”
Section: Resultsmentioning
confidence: 99%
“…Disruption of the LINC complex leads to a loss of mechanical stiffness in Swiss3T3 cells, similar to that seen in Lmna -/-fibroblasts (Broers et al, 2004;Lammerding et al, 2004;Lee et al, 2007;Stewart-Hutchinson et al, 2008). Lmna -/-fibroblasts also have defects in migration and polarization (Houben et al, 2009;Lee et al, 2007). These findings all point to a role for the LINC complex as a linker between the nucleoskeleton Journal of Cell Science 122 (22) (C)Recovery rates are expressed in terms of t 1/2 (see Materials and Methods) for FRAP of GFP-mini-nesprin-2G, GFP-KASH or GFP-KASH DL in the nuclear envelope region of wild-type MEFs (blue columns), Lmna -/-MEFs (red columns) or Lmna -/-cells co-transfected with exogenous RFP-lamin A (yellow columns).…”
Section: Discussionmentioning
confidence: 84%
“…19,40,41 A type lamins have been implicated in nuclear-cytoplasmic interactions because lamin A/C deficient fibroblasts fail to orient their centrosome toward the leading edge, although it was unclear whether this was due to an effect on the centrosome or on the nucleus (or both). 42,43 To explore the role of lamins in nuclear movement, we first tested whether lamins might be found in TAN lines and did not detect accumulation of either endogenous lamin A/C or lamin B1 in TAN lines. Nonetheless, in fibroblasts derived from lamin A/C knockout mice or NIH3T3 fibroblasts acutely depleted of lamin A/C, we observed that the lack of centrosome orientation was due to a defect in nuclear movement.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%